Math, asked by varaghese777, 8 months ago

(m³-n²m)² explain with identities pls note identities​

Answers

Answered by oOfRiEnDsHiPoO
2

Answer:

( {m}^{3}  -  {n}^{2} m) ^{2}  \\  \\ formula \: to \: be \: used \\  \\ (a - b) ^{2}  \\  \\  =  {a}^{2}  - 2ab +  {b}^{2}  \\  \\ here \: a =  {m}^{3}  \\  \\ and \: b =  {n}^{2} m \\  \\ using \: it \: we \: get \\  \\ ( {m ^{3}) }^{2}  - 2 \times  {m}^{3}  \times  {n}^{2} m + ( {n}^{2} m)^{2}  \\  \\  =  {m}^{6}  - 2 {m}^{4}  {n}^{2}  +  {n}^{4}  {m}^{2} \\ \\ =\:m^2 (m^4 - 2m^2n^2 + n^2) \\ \\ = m^4 - 2m^2n^2 + n^2

# keep smiling ☺

Answered by Anonymous
0

Answer:

3445+78898+67778

677/6777+788

Similar questions